2017
DOI: 10.1212/nxi.0000000000000324
|View full text |Cite
|
Sign up to set email alerts
|

Validity of a PCR assay in CSF for the diagnosis of neurocysticercosis

Abstract: Objective:To prospectively evaluate the validity of a PCR assay in CSF for the diagnosis of neurocysticercosis (NC).Methods:We conducted a multicenter, prospective case-control study, recruiting participants from 5 hospitals in Cuenca, Ecuador, from January 2015 to February 2016. Cases fulfilled validated diagnostic criteria for NC. For each case, a neurosurgical patient who did not fulfill the diagnostic criteria for NC was selected as a control. CT and MRI, as well as a CSF sample, were collected from both c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…The use of DNA-based techniques for NCC diagnosis has been reported ( 4 , 10 , 11 ). A recent polymerase chain reaction (PCR) assay study showed excellent sensitivity and specificity in the diagnosis of extraparenchymal NCC ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of DNA-based techniques for NCC diagnosis has been reported ( 4 , 10 , 11 ). A recent polymerase chain reaction (PCR) assay study showed excellent sensitivity and specificity in the diagnosis of extraparenchymal NCC ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of DNA-based techniques for NCC diagnosis has been reported ( 4 , 10 , 11 ). A recent polymerase chain reaction (PCR) assay study showed excellent sensitivity and specificity in the diagnosis of extraparenchymal NCC ( 11 ). Next-generation sequencing (NGS) of CSF is being used increasingly for the clinical diagnosis of CNS infections ( 12 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the availability of modern neuroimaging methods and reliable immunodiagnostic tests, diagnosis of NCC remains challenging, mainly due to variability in sensitivity and specificity of immunodiagnostic tests and a lack of typical neuroimaging findings in the majority of NCC cases. Detection of T. solium DNA in CSF by conventional PCR has been reported to have high sensitivity and specificity in Latin America [ 10 , 11 ], especially, for extraparenchymal NCC [ 12 ]. However, such assays typically require an a priori suspicion of T. solium infection.…”
Section: Discussionmentioning
confidence: 99%
“…44 53 Increased risk for severe Strongyloidiasis is associated with marked immunosuppression. 44 53 Increased risk for severe Strongyloidiasis is associated with marked immunosuppression.…”
Section: P a R Asi T Ic I Nf E Cti On Smentioning
confidence: 99%
“…Nevertheless, molecular analysis of CSF can also accurately identify patients with extraparenchymal infection. 44 CNS infection may present with myelitis, encephalitis, and/or meningitis. 49 Antibodies against Toxocara spp.…”
Section: P a R Asi T Ic I Nf E Cti On Smentioning
confidence: 99%